A Competent, Atom-Efficient and Sustainable Synthesis of Bis-Coumarin Derivatives Catalyzed over Strontium-Doped Asparagine Modified Graphene Oxide Nanocomposite. (26th November 2022) - Tamoradi, Taiebeh; Mohammadi, Masoud; Kiasat, Ali Reza; Davarpanah, Jamal; Karmakar, Bikash
Abstract: In this work, a novel strontium-asparagine (Asn) complex has covalently immobolized over the surface of graphene oxide via post synthetic modification approach. Sr was introduced in the material in order to provide a basic environment. Asn has been a very good template to stabilize the Sr species in the complex. Structural features of the material was investigated by different methods like FT-IR, SEM, EDX, elemental mapping, TEM and TGA. The as-synthesized nanocomposite was successfully employed in the synthesis of diverse bis-coumarins or dicoumarols by assembling 4-hydroxycoumarin and different aromatic aldehydes. The product was obtained in refluxing EtOH in outstanding yields and within very short time. In order of reusability, the catalyst was retrieved by centrifuger and recycled 5 successive times without appreciable loss in its activity. Heterogeneity of the material was studied by hot filtration test. The bis-coumarin products were obtained just by recrystallization form hot EtOH and there was no requirement of column chromatography in isolating the pure product. Graphical Abstract: UF0001